KONVERSI AGAMA DAN PEMAHAMAN NILAI ISLAM SANTRI PONDOK ITIKAF JAMA’AH NGAJI LELAKU LAWANG - Redhani, Ahmad (Faculty of Ushuluddin and Humanities, 2017)
Pondok Itikaf Jama'ah Ngaji Lelaku, Lawang is one of the containers to learn and understand Islam, the background of santri like people who have a black background, such as ex-thugs, gamblers, drunkards, people who have problems of life and people who want to learn religion But have limitations in Arabic. The way santri learn religion, that is by trying to understand the holy verses of the Qur'an and hadith, one of his understanding that is belief in performing the congregational prayer accompanied by the language translation of his people, this is contrary to the prevailing Islamic law. The purpose of the research is to find out 1) why the subject is interested to join the Pondok Itikaf Jama'ah Ngaji Lelaku, Lawang, 2) the psychological factors that cause the students of Pondok Itikaf Jama'ah Ngaji Lelaku, Lawang change beliefs bergama, 3) how the process of belief change students santri Itikaf Jama'ah Ngaji Lelaku, Lawang, and 4) how the understanding of Islamic values of Santri Pondok Itikaf Jam'ah Ngaji Lelaku, Lawang.The research method used is single case study method. Data collection is done through interview, observation, and documentation. Data analysis is done by using descriptive analysis, that is using words to describe what the purpose of this research. The results showed that 1) subjects interested in joining and believing to implement the teachings received in the cottage because the subject is acceptable as it is by the manager of the cottage, the manager also patient and painstaking provide guidance on the subject, the subjects at least get the peace of mind and can change the attitude of the subject, At least get the peace of mind and can change the attitude of the subject to a better direction, there is a common background between students who are with each other. 2) psychological factors causing the subject to change beliefs, subjects experiencing symptoms of inner pressure caused by the emotional attitudes of the subject, it encourages subjects to seek inner calm by way of learning and reciting to understand the purposes of the holy verses of the Qur'an and hadith and try Implement it. 3) the process of changing the subject's beliefs. In the quiet period, subjects are apriori towards religion. The period of unrest, the subject felt the religion that he believed could not be the handle of life. The conversion period occurs after the subject's conflict subsides and the subject can define a new belief. Calm and serene period, subjects gained the composure of the new doctrine. The period of conversion expression, subjects are subject and harden their behavior with new teachings. 4) overall awareness of religion students of Pondok Itikaf Jama'ah Ngaji Lelaku, Lawang not yet mature